Effective Block Signal Interpolation Algorithm - Kazlauskas, K. (Elektronika ir Elektrotechnika, 2000)
It is shown that interpolation algorithm with fast Fourier transform (FFT) don’t satisfy symmetry condition, and it produces interpolated signals with nonzero imaginary components. Block interpolation algorithm satisfies symmetry condition, and the sizes of FFT and inverse FFT are integer powers of 2. Block interpolation algorithm is more efficient in a sense of the multiplication operation number.